Borderline and cluster C personality disorders manifest distinct physiological responses to psychosocial stress. (October 2016) - Aleknaviciute, Jurate; Tulen, Joke H.M.; Kamperman, Astrid M.; de Rijke, Yolanda B.; Kooiman, Cornelis G.; Kushner, Steven A.
Highlights: Women with BPD and CPD report a similar burden of subjective mood disturbance. BPD and CPD are associated with qualitatively distinct psychophysiological reactivity. BPD patients have significantly reduced cortisol and heart rate reactivity. CPD patients have no discernible psychophysiological alterations. Abstract: Background: Maladaptive emotional control is a defining feature of personality disorders. Yet little is known about the underlying physiological dynamics of emotional reactivity to psychosocial stress across distinct personality disorders. The current study compared subjective emotional responses with autonomic nervous system and HPA axis physiological responses to psychosocial stress in women with cluster C personality disorder (CPD) and borderline personality disorder (BPD). Methods: Subjective mood ratings, salivary cortisol, heart rate (HR), and skin conductance level (SCL) were assessed before, during, and after exposure to a standardized psychosocial stress paradigm (Trier Social Stress Test, TSST) in 26 women with BPD, 20 women with CPD, and 35 healthy female controls. Subjects were free of any medication including hormonal contraceptives, had a regular menstrual cycle, and were tested during the luteal phase of their menstrual cycle. Results: Both CPD and BPD patients reported a similar burden of subjective mood disturbance. However, only BPD patients demonstrated reduced baseline cortisol levels with a blunted cortisol and HR reactivity to the TSST. In addition, BPD patients exhibited a generalized increase of SCL. No significant differences in baseline or TSST reactivity of cortisol, HR, or SCL were observed between CPD patients and healthy controls. Conclusion: These findings indicate that patients with BPD have significant alterations in their physiological stress reactivity, which is notably distinct from patients with CPD and those of healthy controls.